Fungsi Lembaga Adat Du’a Mo’an Watu Pitu dalam Penyelesaian Kejahatan Perkosaan terhadap Anak dalam Masyarakat Adat Sikka - Dangki Wanto Silla; Jimmy Pello; Rudepel Petrus Leo (LPPM Universitas Sains dan Teknologi Komputer, 2024)
The purpose of this research is to analyze the function of the Du'a Mo'an Watu Pitu Customary institution in resolving crimes of rape against children in Sikka Customary society. This research method is empirical juridical. The writing approach is Juridical Sociological, with the writing location at the Customary Institution Du'a Mo'an Watu Pitu, Nangatobong Village, Waigete Sub-district, Sikka Regency. The aspects studied are to find out the supporting factors and how the process of solving the crime of rape in traditional institutions. The data collected are direct interview to the customary leader and also documentation studies in the form of scientific papers and journals to support the writing process. The results of this study are that indigenous peoples tend to choose customary institutions because these institutions are a forum that allows them to maintain their cultural identity and customary values inherited by their ancestors, namely honest customs, The settlement process is with the report of the community's family to the Chairperson of the Du'a Mo'an Watu Pitu Customary Institution in Nangatobong Village, summoning the parties by the Customary institution, the Naruk and Pla Pina process (Customary Case Title), the process of determining sanctions based on the type of rape, signing the minutes of the perpetrator's party has the obligation to carry out